2020
DOI: 10.1016/j.ebiom.2020.102961
|View full text |Cite
|
Sign up to set email alerts
|

Long-term robustness of a T-cell system emerging from somatic rescue of a genetic block in T-cell development

Abstract: Backgound The potential of a single progenitor cell to establish and maintain long-term protective T-cell immunity in humans is unknown. For genetic disorders disabling T-cell immunity, somatic reversion was shown to support limited T-cell development attenuating the clinical phenotype. However, the cases reported so far deteriorated over time leaving unanswered the important question of long-term activity of revertant precursors and the robustness of the resulting T-cell system. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Even though the reversion is observed in all three siblings, differences in their genetics, epigenetic profile and environmental conditions might explain the disparity between P1 symptoms and the rest of the brothers. We conclude that the reversion allows the restoration of T-cell function and immunity for at least 26 years of P1 who is the longest surviving case in comparison with atypical X-SCID patients reported with IL2RG reversion till now [ 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The precursor cells from the patients were not studied nor analyzed in this study due to ethical reasons.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Even though the reversion is observed in all three siblings, differences in their genetics, epigenetic profile and environmental conditions might explain the disparity between P1 symptoms and the rest of the brothers. We conclude that the reversion allows the restoration of T-cell function and immunity for at least 26 years of P1 who is the longest surviving case in comparison with atypical X-SCID patients reported with IL2RG reversion till now [ 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The precursor cells from the patients were not studied nor analyzed in this study due to ethical reasons.…”
Section: Discussionmentioning
confidence: 83%
“…It can be widely observed that reverted mutations in the IL2RG gene can display within a large range of clinical and immunological findings. Patients with low T- and NK-cell counts are documented with T452C, A284-15G and T455C mutations [ 10 , 17 , 23 ], normal STAT5 phosphorylation is reported for a patient with T466C mutation [ 19 ], and even normal TCR repertoire in patients with A655T and T343C mutations [ 16 , 20 ]. Therefore, it is important to underline the differential diagnosis of SCID variants in terms of functional and clinical characterization beyond the infant period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the reversion was not observable in the Sanger sequencing of the PBMCs or, more specifically, in other lymphocyte types (such as NK cells or B cells) and phagocytic cells (like monocytes or macrophages) led us to assume that the natural reversion only occurred in early progenitor T cells and was absent in hematopoietic stem cells. Although the clinical benefit of immune reconstitution in X-SCID patients with reverted mosaicism is improved by the presence of revertant cells [ 5 , 6 , 7 , 8 , 9 , 11 ], the illness progression of several patients still worsened with age [ 10 , 12 ]. As a result, the stability of revertant cells is not assured.…”
Section: Discussionmentioning
confidence: 99%
“…Without any treatment, the risk of death is very high within the first year of life [ 2 , 3 ]. On the other hand, atypical X-SCID patients present a milder form of immunodeficiency due to either hypomorphic mutations [ 4 ] or natural correction induced by somatic reversions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The current treatment of X-SCID includes prophylaxis for infections to ensure the safety of patients and hematopoietic stem cell transplantation (HSCT) to reconstruct their immune function [ 2 ].…”
Section: Introductionmentioning
confidence: 99%